A novel membrane-disruptive antimicrobial peptide from frog skin secretion against cystic fibrosis isolates and evaluation of anti-MRSA effect using Galleria mellonella model - Yuan, Yipeng; Zai, Yu; Xi, Xinping; Ma, Chengbang; Wang, Lei; Zhou, Mei; Shaw, Chris; Chen, Tianbao (Biochimica et biophysica acta. General subjects, 2019)
Antimicrobial peptides from amphibian skin secretion are a promising source for the development of alternative antibiotics against the urgent antibiotic resistance. Methicillin-resistant S. aureus (MRSA) has been found to persist in both early and late disease course of cystic fibrosis (CF). Japonicin-2LF was isolated from the skin secretion of Fujian Large-headed Frog (Limnonectes fujianensis) via the combination of cDNA cloning and MS/MS sequencing. The antimicrobial and anti-biofilm activities of Japonicin-2LF were evaluated using both reference and clinic isolated strains. The permeability of the cell membrane treated by the peptide was revealed by fluorescent staining. The cytotoxicity was examined by haemolysis, MTT and LDH assays. Wax moth larvae (Galleria mellonella) infection model was applied to assess the efficacy of Japonicin-2LF against the reference and clinic MRSA isolates in vivo. Japonicin-2LF exhibited potent antimicrobial activity, particularly against Gram-positive bacteria Staphylococcus aureus and MRSA, killing the bacteria via membrane permeabilisation. Additionally, Japonicin-2LF demonstrated the inhibition and eradication of biofilms, particularly against the biofilm of MRSA by eradicating the biofilm matrix as well as killing all the sessile bacteria. In the in vivo assay, Japonicin-2LF significantly decreased the mortality of MRSA acute infected larvae. In conclusion, it is a novel antimicrobial peptide discovered from the skin secretion of Limnonectes fujianensis, and particularly effective against both planktonic and sessile MRSA. The further in vivo study suggests that Japonicin-2LF could be a potential drug candidate to control the MRSA infection in cystic fibrosis patients. •Discovery of a novel antimicrobial, Japonicin-2LF, with potent inhibition against CF isolates•Japonicin-2LF permeabilized the membrane of bacteria and fungi.•Japonicin-2LF reduced the mortality of MRSA acute infected larvae.